Socio-Pedagogical Prerequisites for Fitness-Industry Funсtioning in Belarus - V. V. Sadovnikova (OVS LLC, 2018)
The purpose of our questionnaire is the uncovering of prerequisites for recognizing fitness as a format of mass physical education. Materials and methods. We questioned 100 respondents ranging in age from 20 to 60, with work experience from 1 to 40 years, more than 60% of the respondents have work experience from 5 to 20 years, and different specialization of work with population (aerobic, strength, competitive, oriental, water kinds of physical activity). The results were processed with statistical distribution-free methods (х²). When the number of testees exceeded 100 (n=100), we used the method of Kolmogorov-Smirnov under normal distribution of selection. Results. In accordance with the demand, aerobics and strength training occupy the 1st place, 30% and 40%, respectively. At the 2nd place, we have trouble zones exercises for women, swimming and water aerobics - 30% and 28%, respectively. At the 3rd place - sports and outdoor games, stretching - 18% and 13%, respectively. The other forms received less than 8%. The forms presented were evaluated in points, all the points were summed. In general, the demand is estimated to be 1.99±1.31 points out of 12 possible, indicating the specialization in working with the population through the use of fitness technologies, based on 3-4 types of physical activity. Conclusions. We think that the development of mass sport, sport for everybody, fitness as a means of health improvement is a prerogative of the Government via local authorities, sport organizations, institutions at this level, and, of course, the population.  In our opinion, fitness in Belarus functions independently but unsystematically, it develops unilaterally - it is self-organized in the process and in the use of fitness technologies only. The work on intentional development of and managing this form of mass physical education within the system is necessary.